The Effect of Peer Group Discussion on Increasing Awareness in Preventing Sexual Risk of HIV/AIDS in Students at SMA Negeri 1 Gorontalo - Isra Nur; Herlina Jusuf; Nirwanto K. Rahim (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Human Immunodeficiency Virus (HIV) is a virus that attacks white blood cells and weakens the human immune system, while acquired immunodeficiency syndrome (AIDS) is a set of symptoms that arise as a result of HIV infection that has weakened the immune system. This study aims to analyze the influence of peer group discussion on increasing awareness in preventing HIV/AIDS risky sexual behavior in students of SMA Negeri 1 Gorontalo. The method used is quantitative research with a pre-experimental design using a one-group pre-test and post-test approach. The sample totaled 20 students who were selected through purposive sampling technique. The results showed that before the intervention, the majority of students (80%) were in the category of moderate consciousness, 15% in high consciousness, and 5% in low consciousness. After the intervention, there was a significant improvement, with 95% of students in the high awareness category and only 5% still in the medium category. A statistical test using a paired t-test showed a significance value of 0.000 (p < 0.05), which means that there is a significant effect of peer group discussion on increasing awareness. The discussion activity which was carried out three times with a duration of 60 minutes was proven to be able to increase knowledge, form positive attitudes, and encourage changes in student behavior in preventing risky sexual behavior related to HIV/AIDS.